2007
DOI: 10.1093/ecam/nem007
|View full text |Cite
|
Sign up to set email alerts
|

The Medicinal Mushroom Agaricus blazei Murrill: Review of Literature and Pharmaco‐Toxicological Problems

Abstract: Agaricus blazei Murrill (ABM) popularly known as 'Cogumelo do Sol' in Brazil, or 'Himematsutake' in Japan, is a mushroom native to Brazil, and widely cultivated in Japan for its medicinal uses, so it is now considered as one of the most important edible and culinarymedicinal biotechnological species. It was traditionally used to treat many common diseases like atherosclerosis, hepatitis, hyperlipidemia, diabetes, dermatitis and cancer. In vitro and in vivo ABM has shown immunomodulatory and antimutagenic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
195
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(211 citation statements)
references
References 92 publications
(109 reference statements)
2
195
1
9
Order By: Relevance
“…Agaricus blazei contains active organic compounds associated with the maintenance of human health and the healing of diseases. Pharmacological studies have shown that bioactive substances, such as polysaccharide-protein complexes (PSPC) from A. blazei, function as antioxidants, antimutagenics, antitumorigenics, and anticancer agents (Kimura et al, 2004;Firenzuoli et al, 2008). However, the harvesting time of A. blazei is relatively long (approximately 60 days) when compared to other related Agaricus sp., including A. bisporus (approximately 30 days) (Pardo-Gimenez et al, 2010;Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Agaricus blazei contains active organic compounds associated with the maintenance of human health and the healing of diseases. Pharmacological studies have shown that bioactive substances, such as polysaccharide-protein complexes (PSPC) from A. blazei, function as antioxidants, antimutagenics, antitumorigenics, and anticancer agents (Kimura et al, 2004;Firenzuoli et al, 2008). However, the harvesting time of A. blazei is relatively long (approximately 60 days) when compared to other related Agaricus sp., including A. bisporus (approximately 30 days) (Pardo-Gimenez et al, 2010;Chu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have shown that bioactive substances, such as polysaccharides and polysaccharide-protein complexes, in A. blazei, function as antioxidants, antimutagenics, antitumorigenics, and anticancer agents (Izawa & Inoue, 2004;Kimura et al, 2004;Firenzuoli et al, 2008). Therefore, it is not surprising that A. blazei has drawn the attention of food scientists and biotechnologists.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of sawdust and PS, which involves tree farming and mining of the natural resource, poses serious threats to the environment and, at the same time, increases production costs. In addition, the accumulation of heavy metals to toxic levels, which are often associated with A. blazei, is speculated to be related to the applied culture media and casing soil (Firenzuoli et al, 2008;Huang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mushroom Agaricus brasiliensis, also known as A. blazei or A. subrufescens (Wasser et al, 2002;Kerrigan, 2005;Dias et al, 2008), has received great interest since the end of the 20th century, and several papers were recently published highlighting its medicinal properties (Kawagishi et al, 1989;Mizuno et al, 1990aMizuno et al, ,b, 1995Ito et al, 1997;Kaneno et al, 2004;Mizuno & Kawakami, 2006;Fan et al, 2007;Firenzuoli et al, 2008).…”
Section: Medicinal Mushroom (Agaricus Brasiliensis)mentioning
confidence: 99%